2000
DOI: 10.1021/bi992065o
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Substrate Binding to the Chaperone SecB

Abstract: The thermodynamics of binding of unfolded polypeptides to the chaperone SecB was investigated in vitro by isothermal titration calorimetry and fluorescence spectroscopy. The substrates were reduced and carboxamidomethylated forms of RNase A, BPTI, and alpha-lactalbumin. SecB binds both fully unfolded RNase A and BPTI as well as compact, partially folded disulfide intermediates of alpha-lactalbumin, which have 40-60% of native secondary structure. The heat capacity changes observed on binding the reduced and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 51 publications
3
28
0
Order By: Relevance
“…Thus, the data is consistent with a model that the B-chain is bound on the surface of the chaperone SecB in a flexible extended state. In certain cases it has been shown that SecB binds to partially folded conformations of proteins such as ␣-lactalbumin and barstar (8,10). In the present work we suggest that the bound conformation is an extended conformation.…”
Section: Thermodynamic Coupling Model Of B-chain Dissociation Bysupporting
confidence: 53%
See 3 more Smart Citations
“…Thus, the data is consistent with a model that the B-chain is bound on the surface of the chaperone SecB in a flexible extended state. In certain cases it has been shown that SecB binds to partially folded conformations of proteins such as ␣-lactalbumin and barstar (8,10). In the present work we suggest that the bound conformation is an extended conformation.…”
Section: Thermodynamic Coupling Model Of B-chain Dissociation Bysupporting
confidence: 53%
“…The two results are not necessarily contradictory because of the very short length of the binding frame. Since SecB binds only small 10-residue regions of the substrate and the binding site on SecB is solvent accessible (10) it is possible for the bound fragment to be extended even though the remainder of the protein adopts a relatively compact conformation. Recent NMR studies of the ␣-lactalbumin molten globule have also shown that some regions of the molten globule adopt an unfolded conformation (33).…”
Section: Thermodynamic Coupling Model Of B-chain Dissociation Bymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the model protein substrate, barstar, revealed that SecB does not bind the folded or unfolded state but traps a near native-like molten globule state (6). SecB has also been shown to bind partially folded states of lactalbumin (9).…”
mentioning
confidence: 99%